Effect of erytropoietin therapy on left ventricle mass and end stage small disease underwent hemodyalisis (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
Cardiovascular disease is the most common cause of death in patients maintained on hemodialysis (HD) of end stage renal disease (ESRD). This study was aimed at evaluating the regression of left ventricular mass (LV mass) and blood pressure among ESRD patients underwent HD. A randomized double-blind placebo controlled clinical trial had been done on 32 patients who underwent HD with acetate. Left ventricular mass was examined with Echocardiography interdialitic time. Fifteen patients (11 males and 4 females) with r-HuEpo therapy (group I) and 16 patients (9 males and 7 females) with placebo (group II) were recruited in the study. The mean age group I was 52.27 ÃÂ± 14.69 years and Group II: 46.25 ÃÂ± 9.01 years (95% CI:-2.82 - 14.86; p = 0.117. There was no significant difference in hemoglobin concentration (Hb), hematocrit (Hct), systolic and diastolic blood pressure; LVM at baseline between two groups. After 5 weeks of therapy with r-HuEpo 2000 Unit 2 times/week, the change of mean in hemoglobin concentration in Group I increased: 8.05 ÃÂ± 1.62 mg/dl to 8.39 ÃÂ± 2.160 mg/dl and in Group II decreased 7.38 ÃÂ± 1.2 to 7.13 ÃÂ± 1.75 mg/dl (p = 0.083,NS), Hct: group I increased 22.54 ÃÂ± 7.83% to 25.71 ÃÂ± 6.66%; group II decreased 23.99 ÃÂ± 4.69 to 21.51 ÃÂ± 5.29 (p = 0.061,NS) where as systolic blood pressure in Group I increased from 134.615 ÃÂ± 21.454 mmHg to 140.67 ÃÂ± 27.12 mmHg, group II increased 144.37 ÃÂ± 18.24 mmHg to 146,88 ÃÂ± 26,01 mmHg (p = 0.520, NS); diastolic blood pressure in Group I decreased from 83.076 ÃÂ± 11.821 mmHg to 79.67 ÃÂ± 13.43 mmHg, group II 91.25 ÃÂ± 10.87 mmHg to 90.63 ÃÂ± 15.69 mmHg (p = 0.046, SI; and the LV mass in Group I reduced from 359.15 ÃÂ± 107.49 g to 316.32 ÃÂ± 67.43 g, group II 345.21 ÃÂ± 89.27 to 340.65 ÃÂ± 97.84 g (p = 0.434, NS) respectively. In conclusion, after 5 weeks of therapy r-HuEPO tended to reduce left ventricular mass in ESRD patients with maintenance hemodialysis. Left ventricular mass reduction in this patients may be associated with diastolic blood pressure reduction, increase of hemoglobin concentration and increase of hematocrit decrease of end diastolic diameter.Key words: r-HuEPO - left ventricular mass - hemodialysis - echocardiography - end stage renal disease